From Individual Hostility to Structural Communication Practice: A Qualitative Meta-Synthesis of Digital Misogyny in Communication Studies (2020-2025) - Devi Arianti; Rachmat Kriyantono; Yuyun Agus Riani (FAKULTAS DAKWAH UIN SALATIGA, 2026)
The objective of this study is to examine how communication scholarship conceptualizes digital misogyny as a communication practice within the context of social media. The study responds to the growing academic attention to gender-based hostility in digital environments, which remains conceptually fragmented across existing research. To address this gap, it adopts a systematic conceptual mapping approach to clarify the distinctive contribution of communication studies to the understanding of digital misogyny. This research employs a qualitative meta-synthesis method within an interpretive paradigm, analyzing 155 peer-reviewed international journal articles in the field of communication studies published between 2020 and 2025. An inductive thematic synthesis is used to identify dominant conceptual patterns, variations in misogynistic communication practices, and the ways in which social media is positioned as a digital public space. The findings reveal a consistent conceptual shift from viewing misogyny primarily as an individual attitude toward understanding it as a discursive, cultural, and structurally mediated communication practice. Five core conceptual patterns are identified: misogyny as individual hatred, discursive practice, digital cultural expression, a phenomenon shaped by platform structures, and a mechanism of social control. The results further indicate that digital misogyny operates through both overt and covert practices, with subtle forms such as humor and memes playing a significant role in the normalization of gender inequality. Overall, this study advances a more integrated conceptual framework for understanding digital misogyny as a symbolic, mediated, and structurally embedded phenomenon within the digital public sphere.